Overweight and obesity on the island of Ireland: an estimation of costs. Issue 3 (16th March 2015) - Dee, Anne; Callinan, Aoife; Doherty, Edel; O'Neill, Ciaran; McVeigh, Treasa; Sweeney, Mary Rose; Staines, Anthony; Kearns, Karen; Fitzgerald, Sarah; Sharp, Linda; Kee, Frank; Hughes, John; et al.
Abstract : Objectives: The increasing prevalence of overweight and obesity worldwide continues to compromise population health and creates a wider societal cost in terms of productivity loss and premature mortality. Despite extensive international literature on the cost of overweight and obesity, findings are inconsistent between Europe and the USA, and particularly within Europe. Studies vary on issues of focus, specific costs and methods. This study aims to estimate the healthcare and productivity costs of overweight and obesity for the island of Ireland in 2009, using both top-down and bottom-up approaches. Methods: Costs were estimated across four categories: healthcare utilisation, drug costs, work absenteeism and premature mortality. Healthcare costs were estimated using Population Attributable Fractions (PAFs). PAFs were applied to national cost data for hospital care and drug prescribing. PAFs were also applied to social welfare and national mortality data to estimate productivity costs due to absenteeism and premature mortality. Results: The healthcare costs of overweight and obesity in 2009 were estimated at €437 million for the Republic of Ireland (ROI) and €127.41 million for NI. Productivity loss due to overweight and obesity was up to €865 million for ROI and €362 million for NI. The main drivers of healthcare costs are cardiovascular disease, type II diabetes, colon cancer, stroke and gallbladder disease. In terms of absenteeism, low back pain is the main driver in both jurisdictions, and for productivity loss due to premature mortality the primary driver of cost is coronary heart disease. Conclusions: The costs are substantial, and urgent public health action is required in Ireland to address the problem of increasing prevalence of overweight and obesity, which if left unchecked will lead to unsustainable cost escalation within the health service and unacceptable societal costs.